Exploring the steady operation of a continuous pilot plant for the di-nitration reaction - Sharma, Mrityunjay; Acharya, Roopashree B.; Kulkarni, Amol A (Chemical Engineering & Technology, 2019)
Continuous-flow synthesis of the selective herbicide pendimethalin was demonstrated in both a laboratory-scale and a pilot-scale reactor using only concentrated nitric acid as nitrating agent. The di-nitration reaction follows second-order kinetics where the reaction is first order with respect to both reactant and nitric acid. The pinched-tube reactor was chosen for pilot-scale reactor fabrication due to its excellent mixing and mass transfer characteristics compared to a straight-tube reactor. The estimated mass transfer coefficient showed similar nature in the laboratory-scale and the pilot-scale pinched-tube reactor, ensuring similar performance at the pilot scale. Di-nitration in continuous flow, inline quenching, extraction, and phase separation are some of the salient features of the developed pilot plant. The importance of the start-up time for achieving steady state in the flow system at the large scale is highlighted.